Essential oil constituents of Alpinia mutica Roxb. - Mohd Sirat, Hasnah; A. Rahman, Ahmad (Allured Publishing Corp., 1998)
The oil of Alpinia mutica Roxb was produced by hydrodistillation from fresh rhizomes, collected from cultivated plants in Universiti Pertanian Malaysia. The oil was analyzed by GC/MS and 24 components were identified which constituted 87.5% of the oil. The major components of the oil were camphor (35.6%), 1,8-cineole (9.4%) and borneol (8.3%).